REQUIREMENTS FOR SECURING COMPANY NETWORK INFRASTRUCTURE - Korobeinikova, Tetiana; Luzhetska, Natalia; Kishchak, Marta (Sworld-Us Conference proceedings, 2024)
The paper examines a process for managing risks and information security in an organization. It includes the identification and classification of assets, assessment of potential threats and vulnerabilities, evaluation of the consequences and likelihood of